DEKRIMINALISASI PENGGUNA NARKOBA : POLITIK KRIMINAL PENANGGULANGAN PROBLEMATIKA OVERCAPACITY LEMBAGA PERMASYARAKATAN DI INDONESIA - Maryani, Indah (Universitas Wiralodra, 2021)
Prison overcapacity is one of the crucial legal issues at this time, in this case the overcapacity has reached 204%. The large number of narcotic convicts is one of the causes of prison overcapacity, related to this, narcotics convicts reach 50% of the total inmates in Indonesia. The purpose of this study was to determine the need for drug users, namely abusers and drug addicts to be handled with non-penal efforts and decriminalization of drug abusers in order to reduce the level of overcapacity of prisons in Indonesia. The research method used is normative legal research that prioritizes secondary data. The results of the study confirm that addicts and abusers are victims who are entitled to protection so as not to become victims of criminal acts and have the right to obtain guarantees or rehabilitation for the losses they have received. So that non-penal efforts are needed to protect the rights of victims and decriminalization needs to be done as part of criminal politics to bring criminal law to a better direction, in this case upholding the rights of victims and being a solution to the problem of overcapacity in prisons in Indonesia. Keywords: Overcapacity, decriminalization, rehabilitation